Heritage, Nostalgia and Modern British Theatre - Poore, Benjamin. author. aut Link
IX, 232 p.
Keywords: The stage portrayal of the Victorians in recent times is a key reference point in understanding notions of Britishness, and the profound politicisation of that debate over the last four decades. This book throws new light on works by canonical playwrights like Bond, Edgar, and Churchill, linking theatre to the wider culture at large.